OVERCOMING LANGUAGE BARRIERS IN TEACHING ENGLISH SPEAKING SKILLS (Ustozlar uchun, 2026)
Teaching speaking skills in English is often complicated by various language barriers that learners face in the classroom. These barriers include limited vocabulary, grammatical inaccuracy, pronunciation difficulties, psychological factors such as fear of making mistakes, and insufficient exposure to authentic language use. The present article examines the main causes of language barriers in teaching English speaking skills and analyzes effective strategies for overcoming them. Special attention is given to communicative language teaching, learner-centered approaches, and the role of the teacher in creating a supportive speaking environment. The study emphasizes the importance of reducing anxiety, encouraging interaction, and integrating speaking activities into everyday lessons.